High fidelity core flow measurement experiment for an advanced research reactor using a real scale mockup - Kim, Taeil; Lee, Yohan; Hwang, Donkoan; Jung, WooHyun; Choi, Nakjun; Chung, Seong Seok; Kim, Jihun; Park, Jonghark; Son, Hyung Min; Song, Kiwon; Kim, Huiyung; Jo, HangJin (Nuclear engineering and technology, 2024)
Owing to spatial effects and vortex flow, flow in research reactors that use plate-type fuels can be maldistributed to the parallel channels of the core, which significantly impacts the reactor safety. In this study, the core flow of an advanced research reactor was measured in a real-scale facility under various hydraulic conditions. For flow measurement, integrated pressure lines were embedded in the mockups of 22 fuel assemblies and six fission molybdenum assemblies. Each assembly mockup was individually calibrated to obtain the relationship between the pressure drop and flow rate. Real-scale facility, which implements the characteristics of the hydraulic conditions in research reactors, was then used to evaluate the assembly-to-assembly flow distribution under normal operating condition, a partially withdrawn condition for the follower fuel assemblies, no flow for the pool water management system, and 1:1.5 asymmetric inlet flow condition. As a parallel channel system, core flow distribution was analyzed with conventional header design approach. Taking into account the measuring uncertainty, the core flow was uniformly distributed within 5 % under all conditions. This was mainly because the core flow resistance was sufficiently high and the vortex flow was minimized by the perforated plate.